Estonian education system features - Marcos Francisco Rodríguez Bravo (ADIDE Federación, 2015)
This article attempts to identify structural elements of the Estonian education system which has obtained in the last PISA 2012 international report, some results well above the average set by the OECD (494) and significantly higher than those obtained by Spain . It will also try to outline the causes or reasons that lead to these excellent results, in addition to bring the reader data that can be considered key to understanding the progress of this education system.